Fluorescence detection of dopamine signaling to the primate striatum in relation to stimulus–reward associations - Gaoge Yan; Hidetoshi Amita; Satoshi Nonomura; Ken-ichi Inoue; Wolfram Schultz; Masahiko Takada (Proceedings of the National Academy of Sciences, 2025)
Dopamine (DA) signals to the striatum play critical roles in shaping and sustaining stimulus-reward associations. In primates, however, the dynamics of the DA signals remain unknown since conventional methods are not necessarily appropriate in terms of the spatiotemporal resolution or chemical specificity sufficient for detecting the DA signals. In our study, fiber photometry with a fluorescent DA sensor was employed to identify reward-related DA transients in the monkey striatum. This technique, which directly monitors local DA release, reveals a reward prediction error signal in the anterior putamen originating from midbrain DA neurons. Further, DA transients in the head of the caudate nucleus exhibit a value-based response to reward-predicting stimuli. These signals have been found to arise from two separate groups of DA neurons in the substantia nigra pars compacta. The present results demonstrate that fluorescence DA monitoring is applicable to detect DA signals in the primate striatum for investigating their roles.